Development of Android-based Petmily Application - Tan, Ching Yong; Murli, Norhanifah (Applied Information Technology And Computer Science, 2022)
Pet is a loyal companion animal that always give accompany and entertainment to people especially pet lovers. Pet lovers treat their pet as one of their family members and always record their every moment in photo and post to the social media as a memory. This is because pet can give the advantage in both emotional and physical to pet lovers, for example, pet plays the role as a loyal companion to pet lovers especially for those are alone and feel lonely. The objective of this project is to develop Petmily application in mobile based android platform. The Petmily application is a social and lifestyle application for pet lovers. It is developed in English version. This application serves as a pet social media platform, and at the same time provides pet information platform regarding to common pet emergency and basic obedience pet training. Task recording platform development like a to-do list also included. The methodology used in this development of this Petmily application is Agile model. Generally, the satisfying results with 93.33% positive feedbacks have been obtained from the testing and it can be concluded that Petmily application is accepted by the target users based on the system usability scale. This application will be monitored from time to time to improve the performance and it is hoped that benefits its target users.